Hak Asasi Manusia Islam dan Barat: Studi Kritik Hukum Pidana Islam dan Hukuman Mati - Habib Shulton Asnawi (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2012)
In the human, there is a universal and binding standards. Thus, the principle of respect (to respect), protection (to protect) and fulfillment (to fulfill) Human Rights describes as "jus cogens". That is, a fundamental principle of international law that countries can not be refused because the collective agreement. The principle is the right to life (rigts of live). However, there is particular debate on the universality of Islam and Western standards and there are problems associated with implementing the in practice. Standard of debate in because of the universality of crossing cultural boundaries, particularly religion and each tradition has a frame of reference (frame of reference) and their respective international traditions and norms define the validity of the teachings of their own resources. In this case, the ongoing debate relating to the death penalty law in which Islam and the West has standardized the concept of human rights respectively. Death penalty law contained in the law of Islamic criminal law sharp criticism from the West. Which the death penalty, considered to have a discriminatory character, cruel, inhuman and violating human rights (right to life). This debate, would complicate the enforcement of human rights, especially related to death penalty law, as well as in the plains protection national law enforcement in Indonesia, especially modern law.